Detection of human papillomavirus types in balanitis xerotica obliterans and other penile conditions. Issue 4 (August 1995) - Lau, P W; Cook, N; Andrews, H; Bracka, A; Myint, S H
Abstract : OBJECTIVES--To determine the prevalence of human papillomavirus (HPV) types 6, 11, 16 and 18 in foreskin biopsies from patients with balanitis xerotica obliterans (BXO) and other penile conditions. MATERIALS AND METHODS--Foreskin biopsy specimens from 24 patients with penile lesions and 5 control patients were analysed by type-specific polymerase chain reaction (PCR). RESULTS--HPV6 or HPV16 were not detected in patients with BXO. HPV6 was detected in 2 controls. CONCLUSIONS--Genital papillomaviruses do not have a strong association with BXO.